Keterampilan Literasi Informasi di Era Digital Berdasarkan Model The Big 6 - Moliza Gusriani; Anis Masruri (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The need for information in the digital era is increasing because information is easier to access anytime and anywhere. Efforts that must be applied in order to obtain quality information and as needed, namely by having information literacy skills. Information literacy is the ability to respond and meet information needs. By understanding information literacy, it is expected that the public can receive precise and accurate information. The purpose of this study is to discuss the skills and methods of searching for information needed by each individual. This research uses a type of qualitative research with a descriptive approach supported by literature review in accordance with the topic of this article, namely from books and scientific articles. The result of the discussion of this article is that there is some information on literacy skills models that can be utilized by individuals, as discussed in this article is the Big 6 model which is often used in research, employment, education and others. While the information search technique that can be used easily is the Boolean method.